Elevated Expression of the Integrin-Associated Protein PINCH Suppresses the Defects of Drosophila melanogaster Muscle Hypercontraction Mutants - Pronovost, Stephen M. (Public Library of Science, 2013)
A variety of human diseases arise from mutations that alter muscle contraction. Evolutionary conservation allows genetic studies in Drosophila melanogaster to be used to better understand these myopathies and suggest novel therapeutic strategies. Integrin-mediated adhesion is required to support muscle structure and function, and expression of Integrin adhesive complex (IAC) proteins is modulated to adapt to varying levels of mechanical stress within muscle. Mutations in flapwing (flw), a catalytic subunit of myosin phosphatase, result in non-muscle myosin hyperphosphorylation, as well as muscle hypercontraction, defects in size, motility, muscle attachment, and subsequent larval and pupal lethality. We find that moderately elevated expression of the IAC protein PINCH significantly rescues flw phenotypes. Rescue requires PINCH be bound to its partners, Integrin-linked kinase and Ras suppressor 1. Rescue is not achieved through dephosphorylation of non-muscle myosin, suggesting a mechanism in which elevated PINCH expression strengthens integrin adhesion. In support of this, elevated expression of PINCH rescues an independent muscle hypercontraction mutant in muscle myosin heavy chain, Mhc(Samba1). By testing a panel of IAC proteins, we show specificity for PINCH expression in the rescue of hypercontraction mutants. These data are consistent with a model in which PINCH is present in limiting quantities within IACs, with increasing PINCH expression reinforcing existing adhesions or allowing for the de novo assembly of new adhesion complexes. Moreover, in myopathies that exhibit hypercontraction, strategic PINCH expression may have therapeutic potential in preserving muscle structure and function.